Uremic Toxins in Organ Crosstalk - Lowenstein, Jerome; Nigam, Sanjay K. (Frontiers in Medicine, 2021)
ABSTRACT. Many putative uremic toxins, like indoxyl sulfate, p-cresol sulfate, kynurenic acid, uric acid, and CMPF, are organic anions. Various organic anion transporters (organic anion transporters, OATs; organic anion-transporting polypeptides, OATPs; multidrug resistance-associated proteins, MRPs, and other ABC transporters like ABCG2 mediate movement of uremic toxins through cells and organs. In the kidney proximal tubule, critical roles for OAT1 and OAT3 in regulating levels of protein-bound uremic toxins have been established using knock-out mice. OATs are important in maintaining residual tubular function in chronic kidney disease (CKD). Uremic toxins like indoxyl sulfate also regulate signaling and metabolism, potentially affecting gene expression in non-renal tissues as well as the kidney. Indeed, uremic toxins appear to be part of an extensive “remote sensing and signaling” network--involving so-called drug transporters and drug metabolizing enzymes which modulate metabolism and signaling. This systems biology view of uremic toxins is leading to a new appreciation of uremia as due to disordered remote sensing and signaling mechanisms--resulting from, and causing, aberrant inter-organ (e.g. gut-liver-kidney-CNS) and inter-organismal (e.g. gut microbiome-host) communication. There is a new appreciation of the role of the kidney in organ cross-talk and inter-organismal communication (eg. gut microbiome-host) mediated by small organic molecules. Many of these molecules are organic anions that transported by renal (eg. OAT1) and non-renal transporters ( OATP1B1) and altered by Phase 1 and Phase 2 drug metabolizing enzymes (DMEs); many of these molecules also have well-described roles in metabolism, signaling, and modulation of redox state (1). Among these are so-called protein-bound uremic toxins (eg. indoxyl sulfate, kynurenate, CMPF, phenyl sulfate, p-cresol sulfate, uric acid), which accumulate in chronic kidney disease (CKD) as tubular secretion declines. One of the most fascinating aspects of current research in the field is the multifaceted nature of these uremic toxins and their roles in “remote sensing and signaling” between organs and organisms. Here, we detail a few examples from a systems biology perspective with an emphasis on how they illustrate aspects of the Remote Sensing and Signaling Theory.